4d → 4f resonance in photoabsorption of cerium ion Ce3+ and endohedral cerium in fullerene complex Ce@C82+. (30th August 2016) - Schrange-Kashenock, G
Abstract: The theoretical investigation of the single-photoionization spectra in the 4 d -resonance region (120–150 eV) for the ionic cerium Ce 3+ and cerium in the endohedral complex Ce @ C 82 + (in practice, Ce 3 + @ C 82 2 − ) is presented. The fullerene cage is modeled by ab initio spherical jellium shell with an accurate account for the real distribution of carbon electron density. The oscillator strengths are calculated within the multiconfiguration Dirac–Fock (MCDF) approach for phototransitions from the outermost shells of the ion Ce 3+ with and without the influence of the potential generated by a fullerene cage. It is shown that the integrated oscillator strengths have the main contribution from the Ce 3+ 4 d → 4 f (ten possible from the phototransitions F 7/2, 5/2 2 → D 3/2, 5/2 2, F 5/2, 7/2 2, G 5/2, 7/2 2 ) resonance photoexcitations. The corresponding precise MCDF values for the oscillator strengths and the transition energies are presented for the first time. It is demonstrated that the resonance f 4 d → 4 f oscillator strengths are slightly affected by the presence of the cage potential, despite the fact that the spectral levels structure is changed when the effect of this potential is included. The Auger 4 d −1 decay from the cerium free ion Ce 3+ and the encapsulated endohedral ion Ce 3+@ are considered within the two-step model and the corresponding Lorentzian profiles are presented. This model clearly reveals the correspondence of the complex resonance profile in the Ce 3+ photoabsorption to the fine structure of ion energy levels. The smoothing of the resonance profile in the photoabsorption of the endohedral system Ce @ C 82 + compared with the free ion Ce 3+ is attributed to increasing the linewidths of the Auger transitions. This increase is estimated from the relevant experiment (Müller et al 2008 Phys. Rev. Lett. 101 133001 ) to be strong; as at least three times the value for an isolated ion. The presence of the confining fullerene cage decreases the autoionizing giant 4 d → 4 f resonance lifetime for endohedral cerium in Ce @ C 82 + due to the opening of additional decay channels involving electrons of the fullerene shell, which cannot be accounted as a static potential. From consideration of the two-step model, it is clear that these processes are important. However, they lead only to broadening of the resonance. The dramatic reduction in the integrated oscillator strength in the cerium 4 d resonance region can only occur when additional processes besides photoionization come into play.